(untitled) (Clinics, 2013)
OBJECTIVES: Intestinal neovascularization and abnormal abdominal arterial flow rates have been reported in Crohn's disease. The aim of this study was to evaluate Doppler sonography as a method for assessing Crohn's disease activity based on changes in splanchnic hemodynamics. METHODS: Forty-eight patients with Crohn's disease, 22 healthy volunteers and 12 patients with irritable bowel syndrome were evaluated by Doppler ultrasound for flow parameters of the aorta and superior mesenteric artery. This evaluation included the cross-sectional area, maximum flow volume, peak systolic velocity, end diastolic velocity, resistance and the pulsatility index. Disease activity was classified according to the Crohn's disease activity index. RESULTS: Most measurements in the aorta and superior mesenteric artery were significantly different between Crohn's disease patients and both control groups. Only the aortic maximum flow volume (CC = 0.37, p = 0.009) and aortic peak systolic velocity (CC = 0.30, p = 0.035) showed a significant positive correlation with the Crohn's disease activity index. The determination of cut-off points for the aortic maximum flow volume and peak systolic velocity measurements increased the sensitivity (80 and 75% for flow volume and velocity, respectively), specificity (57 and 75%), accuracy (67 and 75%) and positive (57 and 68%) and negative (80 and 81%) predictive values. These cut-off values permitted the correct classification of most of the patients with Crohn's disease with respect to disease activity. None of the superior mesenteric artery measurements were able to discriminate patients in relation to disease activity. CONCLUSION: The aortic maximum flow volume and peak systolic velocity levels estimated by Doppler sonography reflected disease activity in Crohn's disease. Doppler sonography of the aorta is therefore a novel noninvasive adjunct method that may be useful in the clinical follow-up of patients with Crohn's disease.